THE COMMUNITY EMPOWERMENT THROUGH THE DIGITAL OF ARABIC APPLICATIONS HAJJ & UMRAH AT RAUDHOTUL QURAN ISLAMIC BOARDING SCHOOL, JATINANGOR, WEST JAVA - Rustiman, Uus; Helen, Afrida; Firmansyah, Eka Kurnia (International Journal of Engagement and Empowerment (IJE2), 2023)
This community service activity aims to introduce the Hajj & Umrah The Digital of Arabic Application for the Hajj & Umrah Guidance Group (KBIH) at the Raudhotul Quran Islamic Boarding School, Jatinangor, West Java. This community service aims to provide socialization, training, and mentoring for teachers, Santri, and Hajj and Umrah congregants at the Raudhotul Quran Islamic Boarding School in Jatinangor, West Java. This service is carried out in collaboration with the Hajj and Umrah Guidance Group (KBIH). The material is delivered using Infocus and a projector in PowerPoint form. Results. The results of the activity carried out on November 24 2023 found that the Teachers, Santri and Hajj & Umrah Jama'ah of the Hajj & Umrah Guidance Group (KBIH) Raudhotul Quran Islamic Boarding School Jatinangor West Java were more enthusiastic and motivated to recognize the Hajj & Arabic Digital Application Umrah is further in its application and implementation in daily life, especially for Hajj and Umrah pilgrims as preparations in terms of language towards Mecca al Mukarromah. As a result of this community service activity, it is possible to conclude that this outreach activity has the potential to increase enthusiasm and high motivation to recognize the Hajj & Umrah Arabic Language Digital Application further among teachers, Santri and Hajj & Umrah Congregants, Hajj & Umrah Guidance Groups (KBIH) Islamic Boarding Schools Raudhotul Quran Jatinangor West Java. The participants' enthusiasm was a defining characteristic of the event